2019
DOI: 10.3389/fphys.2019.00432
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Variant of miR-34a Contributes to Susceptibility of Ischemic Stroke Among Chinese Population

Abstract: miRNAs are small non-coding RNAs modulating gene expression, and variants in miRNA genes are involved in the pathogenesis of ischemic stroke (IS). However, the effect of miR-34a polymorphisms on IS susceptibility has rarely been reported. In the present study, we investigated the association between rs12128240, rs2666433, and rs6577555 of the miR-34a gene and IS susceptibility. Snapshot assay was used to detect miR-34a polymorphisms in 548 IS patients and 560 controls. Relative expression of miR-34a was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…miRNA is a type of non‐coding RNA with a length of about 22 nt, which is the core molecule in the ceRNA hypothesis. It can promote the degradation of mRNAs or inhibit translation by binding with the 3′‐untranslated region (3′‐UTR) of target mRNA and further regulate a variety of biological behaviours 41 . Yan et al 42 found that lncRNA HIX003209 did not directly bind to TLR2, TLR4 and NF‐κB; however, it promoted TLR4/NF‐κB expression in macrophages through the sponge miR‐6089, which was critical for the development of rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA is a type of non‐coding RNA with a length of about 22 nt, which is the core molecule in the ceRNA hypothesis. It can promote the degradation of mRNAs or inhibit translation by binding with the 3′‐untranslated region (3′‐UTR) of target mRNA and further regulate a variety of biological behaviours 41 . Yan et al 42 found that lncRNA HIX003209 did not directly bind to TLR2, TLR4 and NF‐κB; however, it promoted TLR4/NF‐κB expression in macrophages through the sponge miR‐6089, which was critical for the development of rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…The present results revealed that MIR34A rs2666433 AA and AG genotype carriers were 5.7 and 2.8 more likely to develop cancer than GG carriers. A part of one recent publication related to the study of the MIR34A rs2666433 association with ischemic stroke in Chinese population 48 , the impact of this variant on CRC risk (or other types of cancer) has not been reported previously. Interestingly, we also found that nearly 43% of the cancer tissues showed a tendency for G to A shift, and a higher frequency of somatic mutation (92%) was observed in the adenocarcinoma subtype of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Sun et al, suggested that the rs2666433 variant may affect the binding of transcription factors to MIR34A promoter sequences 49 . Furthermore, Wei et al reported that ischemic stroke patients with rs2666433 (AA) genotype had a higher level of miR-34a than those with (GG + GA) genotypes 48 , suggesting that rs2666433 may influence miR-34a expression level in their population. However, we could not find a significant association between the specified microRNA variant and its tissue expression levels in the present samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the controls, the Hcy and NEFA serum levels among IS patients were significantly upregulated. Serum NEFA and Hcy were associated with atherosclerosis and IS formation, and high levels of Hcy and NEFA were correlated to poor prognosis in IS patients (Jickling and Spence 2014 ; Wei et al 2019 ). Wei (Wei et al 2019 ) found that serum Hcy levels were upregulated in IS patients, especially those carrying rs2666433 AA genotype.…”
Section: Discussionmentioning
confidence: 99%